On Lives Lived With Law: Land as Healer - C. F. Black (Law Text Culture, 2016)
Senior Law Man Bill Neidjie asks us to listen carefully to the land, just as Sir Humphrey is asking us to be mindful of the impact of the Land’s capricious nature, for both have a deep understanding of the powerful impact Nature has on human wellbeing. And perhaps it is worth considering that this is why the colonist is obsessed with time and resources, whilst the Indigenous are concerned with place and space. It all comes back to Nature.